Inhibition of Tryptophan Catabolism Is Associated With Neuroprotection During Zika Virus Infection - Marim, Fernanda Martins; Teixeira, Danielle Cunha; Queiroz-Junior, Celso Martins; Valiate, Bruno Vinicius Santos; Alves-Filho, Jose Carlos; Cunha, Thiago Mattar; Dantzer, Robert; Teixeira, Mauro Martins; Teixeira, Antonio Lucio; Costa, Vivian Vasconcelos (Frontiers in Immunology, 2021)
Zika virus (ZIKV) is an arbovirus belonging to Flaviviridae family that emerged as a global health threat due to its association with microcephaly and other severe neurological complications, including Guillain-Barré Syndrome (GBS) and Congenital Zika Syndrome (CZS). ZIKV disease has been linked to neuroinflammation and neuronal cell death. Neurodegenerative processes may be exacerbated by metabolites produced by the kynurenine pathway, an important pathway for the degradation of tryptophan, which induces neuronal dysfunction due to enhanced excitotoxicity. Here, we exploited the hypothesis that ZIKV-induced neurodegeneration can be rescued by blocking a target enzyme of the kynurenine pathway, the Indoleamine 2,3-dioxygenase (IDO-1). RT-PCR analysis showed increased levels of IDO-1 RNA expression in undifferentiated primary neurons isolated from wild type (WT) mice infected by ZIKV ex vivo, as well as in the brain of ZIKV-infected A129 mice. Pharmacological inhibition of IDO-1 enzyme with 1-methyl-D-tryptophan – 1-MT, in both in vitro and in vivo systems, led to significant reduction of ZIKV-induced neuronal death without interfering with the ability of ZIKV to replicate in those cells. Furthermore, in vivo analyses using both genetically modified mice (IDO-/- mice) and A129 mice treated with 1-MT resulted in reduced microgliosis, astrogliosis and Caspase-3 positive cells in the brain of ZIKV-infected A129 mice. Interestingly, increased levels of CCL5 and CXCL-1 chemokines were found in the brain of 1-MT treated-mice. Together, our data indicate that IDO-1 blockade provides a neuroprotective effect against ZIKV-induced neurodegeneration, and this is amenable to inhibition by pharmacological treatment.